Cultural Encounters on China's Ethnic Frontiers - Harrell, Stevan; Project Muse.; Project Muse. (University of Washington Press, 2013)
A civilizing project, as described in this book, is a kind of interaction between peoples, in which one group, the civilizing center, interacts with other groups (the peripheral peoples) in terms of a particular kind of inequality. In this interaction, the inequality between the civilizing center and the peripheral peoples has its ideological basis in the center's claim to a superior degree of civilization, along with a commitment to raise the peripheral peoples' civilization to the level of the center, or at least closer to that level.
Introduction -- Part I. The historiography of ethnic identitiy -- The Naxi and the nationalities question / Charles F. McKhann -- The history of the history of the Yi / Stevan Harrell -- Defining the Miao : Ming, Qing, and contemporary views / Norma Diamond -- Making histories : contending conceptions of the Yao past / Ralph A. Litzinger -- Pere Vial and the Gni-pa̕ : orientalist scholarship and the Christian project / Margaret Byrne Swain -- Voices of Manchu identity, 1635-1935 / Shelley Rigger -- Part II. The history of ethnic identity -- Millenarianism, Christian movements, and ethnic change among the Miao in Southwest China / Siu-woo Cheung -- Chinggis Khan : from imperial ancestor to ethnic hero / Almaz Khan -- The impact of urban ethnic education on modern Mongolian ethnicity, 1949-1966 / Wurlig Borchigud -- On the dynamics of Tai/Dai-Lue ethnicity : an ethnohistorical analysis / Shih-chung Hsieh -- Glossary -- References -- Contributors -- Index.
Issued as part of book collections on Project MUSE.
Includes bibliographical references (p. 333-366) and index.
Description based on print version record.
Keywords: Acculturation -- China; Ethnicity -- China; China -- Social life and customs; China -- Ethnic relations; Electronic books; Electronic books